Aqua{6,6′-dimethoxy-2,2′-[ethane-1,2-diylbis(nitrilomethylidyne)]diphenolato}(4-hydroxybenzoato)manganese(III) - Reshma, R. (International Union of Crystallography, 2009)
The title compound, [Mn(C(18)H(18)N(2)O(4))(C(7)H(5)O(3))(H(2)O)], was synthesized by a template reaction of ethane-1,2-diamine and 3-methoxysalicylaldehyde in presence of manganese(II) 4-hydroxybenzoate. The Jahn–Teller-distorted manganese(III) centre has an octahedral geometry. Extensive O—H⋯O hydrogen-bonding interactions generate a two-dimensional sheet structure parallel to (103).